Transition Analysis to Study the Effect of Cooling Rates on Thermal Stresses for Diffusion Bonded Joints - Abdullah, Awfa Abdul-Rassol (Al-Nahrain Journal of Science, 2013)
In this work the analytical and numerical methods were used to calculate the residual stresses induced in the joint due to the deference in the physical and mechanical properties of the materials, cooling from bonding temperature to room temperature. The residual stresses induced in graphite may be become too high that the joint break down so it takes as major stress in the joint. It was found that the residual stress is affected by the joint geometry and the nickel interlayer thickness. The analytical calculation of the residual thermal stresses in graphite/Inconel 600 and Inconel 600/nickel interlayer/Graphite multilayered was done for bonding temperature Tbond=800oCwith various nickel foil thickness, it found that increasing nickel thickness reduce the thermal residual stresses inside the graphite. Numerical method by FEM was used to estimate the distribution of the maximum residual stresses (first principle stress) in the joint. The results indicate that increasing nickel thickness reduces the maximum tensile residual stress. So the joint thicknesses with graphite (5 mm) /Ni (0.1-0.2)mm/ Inconel600 (5 mm) are convenient.